THE EFFECT OF EASE OF TRANSACTIONS AND DISCOUNTS ON CUSTOMER LOYALTY AND THE IMPACT ON CUSTOMER SATISFACTION OF FUND USERS (CASE STUDY OF CONSUMERS AT KANAYA MOBILE & BRILINK STORES IN SEI RAMPAH) - Yenni Arfah; Yenni Mariani Sinurat; Yomeini Margareth Sagala; Yusen Cindranata (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2024)
This study aims to determine the effect of Ease of Transactions and Discounts on Customer Satisfaction and their impact on Customer Loyalty Dana Users. This research was conducted on Dana users at Kanaya Ponsel & Brilink Stores located in Sei Rampah. Serdang Bedagai. This type of research is a quantitative descriptive research. The research sample was 96 respondents with a sampling technique using a purposive sampling technique. The research data was obtained using a google form questionnaire. The data analysis method uses the path analysis method with the help of the SPSS Statistics 25 analysis program. The results show that: 1). Ease of transaction has a significant effect on customer satisfaction. 2). Discounts have no significant effect on customer satisfaction. 3). The ease of transactions has a significant effect on customer loyalty. 4). Discounts have no significant effect on customer loyalty. 5). Satisfaction Satisfaction has a significant effect on customer loyalty. 6). Customer satisfaction has an impact on the ease of transactions on customer loyalty 7). Customer satisfaction has no impact on discounts on customer loyalty.